Persistence of Cry toxins and cry genes from genetically modified plants in two agricultural soils - Marchetti, Elisa; Accinelli, Cesare; Talamè, Valentina; Epifani, Rosanna (Agronomy for sustainable development, 2007)
The environmental impact of genetically modified crops has been the subject of intense research in the past decade. Since the introduction of insect-resistant crops in 1996, cultivation of this group of genetically modified crops has grown substantially. Most insect-resistant varieties, including corn and cotton, have been engineered to express crystal (Cry) toxins. Although several studies concerning the environmental fate of this group of insecticidal toxins have been conducted during the past decade, conflicting information exists dealing with the persistence of Cry toxins in soil. In the present investigation, the persistence of antilepidopteran Cry1Ab and Cry1Ac toxins in two different agricultural soils was studied. The potential of cry 1 Ab genes to persist in soil was also estimated. The results from this laboratory investigation indicated that the two toxins dissipated rapidly in both the sandy and in the clay loam soil. The two toxins showed similar degradation rates in soil. During the 35-day incubation period, more than 92 and 79% of the initial amount of Cry toxins dissipated in the sandy and clay loam soil, respectively. Extractable fractions of the two toxins were lower in the fine-textured soil with respect to the coarse soil. Reduced recovery efficiency from the clay loam soil and thus bioavailability were presumably involved in the lower decline of Cry toxins in this soil. Investigations conducted with an insect-resistant transgenic corn hybrid showed no detectable levels of cry 1 Ab genes in soil six months after plant harvest.